Phenomenon-Based Teaching and Learning through the Pedagogical Lenses of Phenomenology: The Recent Curriculum Reform in Finland - Vasileios Symeonidis; Johanna F. Schwarz (University of Lower Silesia, 2016)
This paper aims to explore the phenomenon-based approach in teaching and learning, through the pedagogical lenses of phenomenology, the philosophy of phenomena. The phenomenon-based approach has informed the new core curriculum for basic education in Finland, which has officially introduced multidisciplinary learning modules as periods of phenomenon-based project studies. In this paper, we discuss how the specific approach is integrated into the curriculum, its theoretical grounding and its connections to constructivism. We also explore its implications for teaching and learning from a phenomenological perspective. The paper concludes that the responsive relation between teaching and learning is essential when our purpose is educational. Students are part of the learning process, but they do not necessarily initiate it; similarly, teachers cannot fully instruct it. Thus, we need to make meaning of the space between teaching and learning, in an effort to reclaim learning for pedagogy.